Distribuição de LNAPL na zona não saturada em solos tropicais, no município de Rio Claro/SP - Bodelão, Thomás Gerdulo [UNESP] (2014)
Most of the research with contaminated areas was developed in soils of temperate regions, distinct from soils of tropical soils. Thus, there is a need to develop and adapt the existing knowledge to Brazilian situations, such as in residual soils. Accordingly, the main purpose of this work is to evaluate the infiltration in the unsaturated zone of a mixture simulating gasoline with ethanol in a typical tropical soil, observing the variations in migration of the pollutant in the different horizons and the transitions between them, and evaluate the behavior of ethanol and compare its migration to the hydrocarbon. Is for that it was performed in the experimental area of Rio Claro / SP an experiment in field scale simulating a shallow superficial gasoline spill. Considering the complexity of the composition of gasoline, with hundreds of compounds present, it was decided to prepare a mixture with a smaller number of compounds, with physical-chemical properties representative of those of the gasoline. Twenty-seven liters of a mixture consisting of 59,3% hexane, 11,1% of xylene, 11,1% of benzene and 18,5% of ethanol were spilled in a ditch with dimensions of 0,3 m wide x 0,3 m long x 0,3 m deep, 2.63 m above the water table. After 07 days of the spill, the area was excavated in blocks of 0,2 x 0,2 x 0,15 m (20 per layer, totaling 220) and Samples were collected from each block. The soil samples were analyzed for the four compounds of the mixture. Based on the concentrations found in the soil samples, most of the hydrocarbons (benzene, xylenes and hexanes) and the ethanol was retained in the superficial layers, not reaching the water table. The mass found relative to the total mass spilled of hydrocarbons was low (only 2,42% of xylenes was found), while for the ethanol the recovery was total. This occurred probably due to the evenly sampling, method since the homogenization of blocks may not have been sufficient to evenly distribute the residual...